The possibilities of opportunistic cervical screening in the assisted reproductive technology clinic - S. V. Khabarov (Опухоли женской репродуктивной системы, 2022)
Secondary prevention of cervical cancer in the conditions of opportunistic cervical screening by co-testing in 5618 women over 30 years of age allowed to identify a high-risk group of cervical cancer for further examination using viral load assessment, immunocytochemical determination of the level of cancer proteins p16INK4a and Ki-67, extended video colposcopy and cervical biopsy with histological examination of surgical material. The obtained data demonstrated the expediency of changing the testing strategy by integrating the methods tested in the framework of opportunistic screening into the nationwide population screening program for cervical cancer.